From Elements to Function: Toward Unifying Ecological Stoichiometry and Trait-Based Ecology - Meunier, Cédric L.; Boersma, Maarten; El-Sabaawi, Rana; Halvorson, Halvor M.; Herstoff, Emily M.; Van de Waal, Dedmer B.; Vogt, Richard J.; Litchman, Elena (Frontiers in Environmental Science, 2017)
The theories developed in ecological stoichiometry are fundamentally based on traits. On the one hand, traits directly linked to cell/body stoichiometry, such as nutrient uptake and storage traits, as well as the associated trade-offs, have the potential to shape ecological interactions such as competition and predation within ecosystems. On the other hand, traits that indirectly influence and are influenced by nutritional requirements, such as cell/body size and growth rate, are tightly linked to organismal stoichiometry. Despite their physiological and ecological relevance, traits are seldom explicitly integrated in the framework of ecological stoichiometry and, currently, the major challenge is to connect ecological stoichiometry traits with functional traits considered in trait-based ecology. Here, we therefore explore and synthesize existing insights, to develop novel connections between ecological stoichiometry and trait-based ecology. By reviewing key traits and their elemental requirements and illustrating community and ecosystem consequences of variation in elemental balances of traits, we show that unifying the framework of ecological stoichiometry with trait-based ecology sheds light on the interplay between elements and functional traits. Linking elements with functions furthers our understanding of the complex connections between subcellular processes, species interactions, and ultimately ecosystem dynamics.